The Effect of Fermented Rice Rinse Water on The Performance of Peking Ducks and on The Physical Quality of Peking Duck Meat - Meisji Liana Sari; Riswandi Riswandi; Sofia Sandi; Daniel Simatupang; Pradesty Aulia Diah Ayu Prameswari (Fakultas Pertanian, Universitas Syiah Kuala, 2023)
Fermented rice water contains lactic acid bacteria and can act as a probiotic that could decrease the pH of the digestive tracts and affect duck performances. The aim of this study was to determine the effect of fermented rice rinse water on the performance of Peking ducks and to determine the effect of fermenting rice rinse water on the physical quality of Peking duck meat. This research was conducted for 4 months in the experimental animal farm laboratory of the Department of Animal Technology and Industry, Faculty of Agriculture, Universitas Sriwijaya. Hundred Peking daily old duck originated from Lampung were applied to completely randomized design with five treatments: P0 (controls), P1 (water + fermented rice rinse water, 2%), P2 (water + fermented rice rinse water, 4%), P3 (water + fermented rice rinse water, 6%), and P4 (water + fermented rice rinse water, 8%) and each treatment has 4 replications. The parameter observed were weekly feed intake (1177.17 to 1200.67 g), body weight gain (213.78 to 225.06 g) and feed conversion ratio (5.33 to 5.53) and to know physical quality of Peking duck meat the observed parameters were pH, water holding capacity, cooking loss water, and tenderness of Peking duck meat. The results showed that fermented rice rinse water at a dose of 2, 4, 6, and 8% for 7 weeks had no effect (P0.05) on feed intake, weight gain, and feed conversion ratio and could not able to affect the performance of Peking ducks. The result showed that addition of fermented rice rinse water up to 8% drinking water had no effect on all parameters of physical quality of peking duck meat. The pH values ranging from 5.8 to 5.9, water holding capacity (DIA) values ranging from 68.79% to 73.37%, cooking losses ranging from 53.15% to 68.38%, and meat tenderness ranging from 191.80 gf to 322.05 gf. Based on the results of this study, it can be concluded that fermenting rice rinse water up to 8% in Peking ducks has not been able to produce optimal values for pH, water holding capacity, water content, cooking loss, and tenderness.